Preparation method of titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate

By supplying lithium step by step and introducing organic acids, titanium lithium adsorbents are prepared, which solves the problems of low adsorption capacity and slow adsorption rate in the prior art, and achieves the effects of high adsorption capacity and high adsorption rate.

CN116116370BActive Publication Date: 2025-04-25BEIJING ORIGIN WATER FILM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211608525.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2025-04-25
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

The existing titanium lithium adsorbents are hindered from diffusion of lithium sources during high temperatures, and the raw materials are mixed unevenly, resulting in low adsorption capacity and slow adsorption rate, which affects the actual use effect.

Method used

Using the method of step-by-step lithium supply, the titanium source and part of the lithium source are reacted under liquid conditions to prepare an intermediate with a high specific surface area, and then the other lithium source is dissolved into a liquid lithium source with organic acid and mixed with the intermediate, dried and sintered at high temperature to prepare a titanium-based lithium adsorbent.

Benefits of technology

By supplying lithium step by step and introducing organic acids, the full mixing of raw materials and uniform dispersion of lithium ions are achieved, the adsorption capacity and adsorption rate of the adsorbent are improved, and the problems of low adsorption capacity and slow adsorption rate of the adsorbent are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116116370B_ABST
    Figure CN116116370B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate, and belongs to the field of titanium-based lithium adsorption technology. First, a titanium source and a part of a lithium source are reacted under liquid conditions to prepare an intermediate with a high specific surface area, and the other lithium source is dissolved into a liquid lithium source with an organic acid, and then the intermediate and the liquid lithium source are mixed, dried, and sintered at a high temperature to prepare a titanium-based lithium adsorbent. The step-by-step lithium supply method of the present invention allows the raw materials to be fully mixed and evenly mixed, thereby improving the adsorption capacity; the organic acid molecules introduced play a pore-forming effect during the sintering process, effectively reducing the particle size of the powder, reducing agglomeration, increasing the specific surface area of ​​the adsorbent, and further improving the adsorption rate. The problem of low adsorption capacity and slow adsorption rate of the current lithium adsorbent is solved, and the lithium extraction efficiency is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate, and belongs to the technical field of titanium-based lithium adsorption. Background Art

[0002] At present, the main technical methods for extracting lithium from salt lakes include precipitation, membrane separation, calcination and impregnation, solvent extraction and adsorption. Among them, the adsorption method has certain advantages over other methods. It not only has good lithium adsorption selectivity, but also has no special requirements for the magnesium and lithium content in the salt lake brine. It is also low-cost, highly efficient and pollution-free. The process of the adsorption method is to use an adsorbent that is selective for lithium to adsorb lithium in the salt lake brine, and then elute the lithium on the adsorbent to separate lithium ions from other ions. Layered metatitanic acid (H2TiO3) is a commonly used titanium-based adsorbent. It is usually obtained by reacting a lithium salt with a titanium source to obtain a lithium metatitanate precursor, and then acid is used to separate the interlayer Li i + Elute to obtain Li + A lithium metatitanate adsorbent with adsorption capacity. The preparation methods of lithium metatitanate precursors include sol-gel method, hydrothermal synthesis method and high-temperature solid phase method. The first two methods are wet synthesis, which requires complex processes, expensive raw materials and high synthesis costs. The high-temperature solid phase method is a method of mixing lithium source and titanium source powders and calcining them at high temperature to obtain lithium metatitanate. This method is simple to operate, low in cost, low in pollution, and suitable for industrial scale-up.

[0003] The distribution characteristic of elements in my country's salt lakes is a high magnesium-to-lithium ratio. Traditional precipitation, membrane separation and calcination impregnation methods have certain limitations for this type of salt lake. Although solvent extraction can separate lithium from salt lakes with a high magnesium-to-lithium ratio, the use of solvents brings certain risks to subsequent processing and production, and the equipment has high corrosion resistance requirements and high costs.

[0004] The lithium metatitanate precursor prepared by the traditional high-temperature solid phase method has the disadvantages of hindering the diffusion of lithium source to titanium source during the high-temperature process, uneven mixing of raw materials, uncontrollable powder morphology, poor uniformity, easy agglomeration, etc. As a result, the prepared metatitanate adsorbent generally has low adsorption capacity and slow ion exchange rate, which affects the actual use effect. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate. The adsorption method can directly separate lithium ions from salt lake brine, has no strict requirements on the magnesium-lithium ratio, and has simple equipment requirements, low pollution and recyclability. Due to its outstanding advantages, it has received widespread attention.

[0006] The method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps: firstly, a titanium source is reacted with a part of a lithium source under liquid conditions to prepare an intermediate with a high specific surface area; another lithium source is dissolved into a liquid lithium source with an organic acid, and then the intermediate and the liquid lithium source are mixed, dried and sintered at a high temperature to prepare a titanium-based lithium adsorbent.

[0007] The advantages of the present invention are: the step-by-step lithium supply method allows the raw materials to be fully mixed and uniform, thereby increasing the adsorption capacity; on the other hand, the organic acid molecules introduced play a pore-forming effect during the sintering process, effectively reducing the particle size of the powder, reducing agglomeration, increasing the specific surface area of ​​the adsorbent, and further increasing the adsorption rate. The problem of low adsorption capacity and slow adsorption rate of the current lithium adsorbent is solved, and the lithium extraction efficiency is effectively improved.

[0008] (1) A titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate is obtained by step-by-step lithium supply. In the step-by-step lithium supply process, a titanium source is first reacted with a portion of a lithium source to obtain a primary lithium supply product with a high specific surface area, and then the remaining lithium source is converted into a soluble lithium source by an organic acid, and the soluble lithium source is mixed with the primary lithium supply product to make the Li in the lithium source + The product is diffused into the primary lithium supply product to obtain the secondary lithium supply product. Finally, the product is sintered under high temperature conditions to complete the crystal transformation process and obtain a titanium-based lithium adsorbent precursor.

[0009] (2) A method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate is proposed. This method reduces the diffusion resistance of the raw lithium source in the raw titanium source, makes the raw materials more evenly mixed, and the resulting precursor layered structure is more complete, thereby increasing the adsorption capacity. + H + Exchange is easier, thereby increasing the adsorption rate. On the other hand, the organic acid introduced during the high-temperature sintering stage produces volatile gases, which play a pore-forming role, reduce product agglomeration and agglomeration, reduce the particle size of the resulting adsorbent precursor and make the particle size distribution more uniform. + The diffusion rate in the adsorbent is faster, thus improving the adsorption performance.

[0010] (3) The proposed preparation method has a significant effect on improving the adsorption performance, solving the problem of low adsorption capacity and slow adsorption rate of titanium-based lithium adsorbents. In addition, the method is simple to operate and has mild preparation conditions, which is conducive to reducing costs and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] When considered in conjunction with the accompanying drawings, the present invention can be more completely and better understood and many of the accompanying advantages can be easily known by referring to the detailed description below, but the drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention, as shown in the figure:

[0012] Figure 1 It is a schematic diagram of the preparation process of the present invention.

[0013] Figure 2 This is the XRD spectrum of the precursor Li2T iO3 of the present invention.

[0014] Figure 3a This is a microscopic morphology of solid HLi TiO3 in slurry A of the present invention.

[0015] Figure 3b This is a microscopic morphology of the precursor Li2T iO3 of the present invention.

[0016] Figure 4 It is the adsorption curve diagram of the present invention.

[0017] Figure 5 This is the XRD spectrum of the precursor Li2T iO3 of the present invention.

[0018] Figure 6a This is a microscopic morphology of solid HLi TiO3 in slurry A of the present invention.

[0019] Figure 6b This is a microscopic morphology of the precursor Li2T iO3 of the present invention.

[0020] Figure 7 Graph showing the adsorption performance of the adsorbent in the embodiment of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0022] Obviously, many modifications and changes made by those skilled in the art based on the purpose of the present invention belong to the protection scope of the present invention.

[0023] Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0024] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art.

[0025] To facilitate understanding of the embodiments, further explanations will be given below, and each embodiment does not constitute a limitation on the embodiments.

[0026] Example 1: Figure 1 , Figure 2 Figure 3 Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate.

[0027] like Figure 1 As shown, a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps: lithium hydroxide monohydrate LiOH·H2O is dissolved to form a LiOH solution, titanic acid is added to the LiOH solution and heated to form a slurry A HLi TiO3, lithium carbonate Li2CO3 is dispersed to form a Li2CO3 dispersion, tannic acid is added to the Li2CO3 dispersion to form a solution B, slurry A HLi TiO3 is mixed with solution B to form a slurry C, slurry C is sprayed and dried to obtain a mixed powder D, and the mixed powder D is sintered at high temperature and ground to obtain a lithium titanate precursor Li2TiO3.

[0028] A method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate further comprises the following steps:

[0029] Step 1, preparation of lithium metatitanate precursor: using metatitanate as a titanium source, lithium hydroxide and lithium carbonate as lithium sources, respectively, and adopting a step-by-step lithium supply method to prepare an adsorbent precursor.

[0030] Step ①, place 40g-100g LiOH·H2O in a reaction container, pour in 500mL deionized water and stir until dissolved. Slowly add a certain amount of metatitanic acid to the above solution, so that the molar ratio of lithium Li and titanium Ti in the system is 0.9:1-1.3:1, stir evenly and heat and boil for 1-3h, the resulting slurry is recorded as slurry A, and the solid in slurry A is the primary lithium supply product HLi TiO3 by wet chemical method.

[0031] Step ②, disperse 30g-75g lithium carbonate powder in 1L deionized water, stir evenly and slowly add tannic acid. Stop stirring when the slurry completely turns into a transparent viscous liquid, stir for 1-3h, and the resulting solution is recorded as solution B.

[0032] Step ③, slowly pour solution B into slurry A under stirring conditions at room temperature to mix, control the molar ratio of Li to titanium Ti in the slurry to be between 1.8:1 and 2.3:1, and stir for 1 to 5 hours to obtain slurry C. Slurry C is spray-dried with a hot air temperature of 140°C to 200°C and an air outlet temperature of 80°C to 100°C to obtain a mixed powder D.

[0033] Step ④, transfer the powder D to a muffle furnace for sintering, the sintering time is 5 to 10 hours, the sintering temperature is 500 to 900°C, and after cooling in the furnace, the obtained solid is ground and crushed to obtain a high-temperature solid-phase secondary lithium supply product, namely, a lithium metatitanate precursor (Li2TiO3).

[0034] Step ⑤, disperse the Li2TiO3 precursor in deionized water with a slurry concentration of 50g / L, and place it in a heating tank for stirring at a heating temperature of 50°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2 to 3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2TiO3 lithium adsorbent.

[0035] Step 2: Preparation of metatitanate adsorbent: Li + After elution, H2T iO3 lithium adsorbent can be obtained. The specific operation is as follows: disperse the precursor in deionized water with a slurry concentration of 30-80g / L, and place it in a heating tank for stirring at a heating temperature of 40-70°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2-3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2T iO3 lithium adsorbent.

[0036] Example 2: Figure 1 , Figure 2 Figure 3 Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps

[0037] Step 1, preparation of lithium metatitanate precursor: using metatitanate as a titanium source, lithium hydroxide and lithium carbonate as lithium sources, respectively, and adopting a step-by-step lithium supply method to prepare an adsorbent precursor.

[0038] Step ①, place 73.84g LiOH·H2O in a reaction container, pour in 500mL deionized water and stir until dissolved. Slowly add a certain amount of metatitanic acid to the above solution so that the molar ratio of lithium Li and titanium Ti in the system is 1.1:1, stir evenly and heat and boil for 3h to obtain slurry A. The solid in slurry A is the primary lithium supply product HLi TiO3 by wet chemical method.

[0039] Step ②: Disperse 59.11 g lithium carbonate powder in 1 L deionized water, stir evenly and slowly add tannic acid. Stop stirring when the slurry completely turns into a transparent viscous liquid. Stir for 1 hour and then add solution B.

[0040] Step ③, slowly pour solution B into slurry A under stirring conditions at room temperature to mix, control the molar ratio of Li to titanium Ti in the slurry to 2.1:1, and stir for 3 hours to obtain slurry C. Slurry C is spray-dried with a hot air temperature of 140°C and an air outlet temperature of 80°C to obtain mixed powder D.

[0041] Step ④, transfer the powder D to a muffle furnace for sintering, the sintering time is 6 hours, the sintering temperature is 550°C, and after cooling in the furnace, the obtained solid is ground and crushed to obtain a high-temperature solid-phase method secondary lithium supply product, that is, lithium titanate precursor Li2T iO3.

[0042] Step ⑤, disperse the Li2TiO3 precursor in deionized water with a slurry concentration of 50g / L, and place it in a heating tank for stirring at a heating temperature of 50°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2 to 3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2TiO3 lithium adsorbent.

[0043] Step 2: Preparation of metatitanate adsorbent: Li + After elution, H2T iO3 lithium adsorbent can be obtained. The specific operation is as follows: disperse the precursor in deionized water with a slurry concentration of 30-80g / L, and place it in a heating tank for stirring at a heating temperature of 40-70°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2-3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2T iO3 lithium adsorbent.

[0044] The XRD pattern of the precursor obtained in this example is as follows Figure 2Compared with the standard card PDF#33~0831, the precursor obtained is Li2TiO3. The microscopic morphology of the solid HL i TiO3 in slurry A in this embodiment is as follows Figure 3a As shown in Figure 1, HLiTiO3 is a flower ball structure composed of two-dimensional nanosheets, which has high porosity and large specific surface area. The microscopic morphology of the precursor Li2TiO3 is shown in Figure 1. Figure 3b As shown, it can be seen that the obtained precursor is nanoscale particles with uniform particle size distribution.

[0045] Lithium adsorption performance test: The adsorption performance was tested using laboratory self-prepared brine. The components and dosages in the self-prepared brine are shown in Table 1. 5g of the lithium adsorbent in the embodiment was soaked in 1L of laboratory prepared brine and stirred continuously. The water sample was taken every 20min and the lithium content was tested by ICP. When the lithium content in the water sample no longer changed, the adsorption equilibrium was reached. The adsorption curve is shown in Figure 4 As shown, the adsorption reaches equilibrium after 100 min, and the equilibrium adsorption amount is 58 mg / g.

[0046] Table 1 Ion types and contents in laboratory self-prepared brine

[0047]

[0048] Example 3: Figure 1 , Figure 2 Figure 3 Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps:

[0049] Step 1, preparation of lithium metatitanate precursor: using metatitanate as a titanium source, lithium hydroxide and lithium carbonate as lithium sources, respectively, and adopting a step-by-step lithium supply method to prepare an adsorbent precursor.

[0050] Step ①, place 92.3g LiOH·H2O in a reaction container, pour in 500mL deionized water and stir until dissolved. Slowly add a certain amount of metatitanic acid to the above solution so that the molar ratio of lithium Li and titanium Ti in the system is 1.3:1, stir evenly and heat and boil for 3h to obtain slurry A. The solid in slurry A is the primary lithium supply product HLi TiO3 by wet chemical method.

[0051] Step ②: Disperse 73.9 g lithium carbonate powder in 1 L deionized water, stir evenly and slowly add tannic acid. Stop stirring when the slurry completely turns into a transparent viscous liquid. Stir for 1 hour and then add solution B.

[0052] Step ③, slowly pour solution B into slurry A under stirring conditions at room temperature to mix, control the molar ratio of lithium Li to titanium Ti in the slurry to be 2.3:1, and stir for 5 hours to obtain slurry C. Slurry C is spray-dried with a hot air temperature of 180°C and an air outlet temperature of 90°C to obtain a mixed powder D.

[0053] Step ④, transfer the powder D to a muffle furnace for sintering, the sintering time is 3 hours, the sintering temperature is 850°C, and after cooling in the furnace, the obtained solid is ground and crushed to obtain a high-temperature solid-phase method secondary lithium supply product, that is, lithium titanate precursor Li2T iO3.

[0054] Step ⑤, disperse the Li2TiO3 precursor in deionized water with a slurry concentration of 50g / L, and place it in a heating tank for stirring at a heating temperature of 50°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2 to 3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2TiO3 lithium adsorbent.

[0055] Step 2: Preparation of metatitanate adsorbent: Li + After elution, H2T iO3 lithium adsorbent can be obtained. The specific operation is as follows: disperse the precursor in deionized water with a slurry concentration of 30-80g / L, and place it in a heating tank for stirring at a heating temperature of 40-70°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2-3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2T iO3 lithium adsorbent.

[0056] The XRD pattern of the precursor obtained in Example 2 is as follows: Figure 5 Compared with the standard card PDF#33~0831, the precursor obtained is Li2TiO3. The microscopic morphology of the solid HL i TiO3 in slurry A in this embodiment is as follows Figure 6a As shown in Figure 1, HLi TiO3 is a flower ball structure composed of two-dimensional nanosheets, which has high porosity and large specific surface area. Figure 6b As shown, it can be seen that the obtained precursor is nanoscale particles with uniform particle size distribution.

[0057] Lithium adsorption performance test: The adsorption performance was tested using laboratory self-prepared brine. The components and dosages in the self-prepared brine were the same as those in Example 2. 5 g of the lithium adsorbent in Example 2 was soaked in 1 L of laboratory prepared brine and stirred continuously. The water sample was taken every 20 min and the lithium content was tested by ICP. When the lithium content in the water sample no longer changed, the adsorption equilibrium was reached. The adsorption curve is shown in Figure 2. Figure 7 As shown, the adsorption reaches equilibrium after 120 min, and the equilibrium adsorption amount is 50 mg / g.

[0058] Example 4: Figure 1 , Figure 2 Figure 3 Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate adopts a step-by-step lithium supply method. First, a titanium source and a part of a lithium source are reacted under liquid conditions to prepare an intermediate with a high specific surface area; another lithium source is dissolved into a liquid lithium source with an organic acid, and then the intermediate is mixed with the liquid lithium source, dried, and sintered at a high temperature, thereby improving the uniformity of the mixing of the raw titanium source and the lithium source, increasing the dispersion of lithium ions between the precursor lithium metatitanate layers, further improving the utilization efficiency of the raw materials, and effectively improving the adsorption capacity of the adsorbent. By introducing organic acid molecules, the powdered lithium carbonate that is not easily dispersed is dissolved into a liquid state, and the dispersion of lithium Li ions in the lithium metatitanate precursor is improved. At the same time, volatile gases are generated during high-temperature sintering to have a pore-forming effect, making the precursor particle size distribution more uniform and the specific surface area larger, thereby improving the adsorption capacity and efficiency of the adsorbent.

[0059] A method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps: using metatitanic acid as a titanium source, lithium hydroxide and lithium carbonate as lithium sources, respectively, and adopting a step-by-step lithium supply method to prepare an adsorbent precursor, and the specific steps are as follows:

[0060] Step ① Place 40g to 100g of LiOH·H2O in a reaction container, pour in 500mL of deionized water and stir until dissolved. Slowly add a certain amount of metatitanic acid to the above solution so that the molar ratio of lithium Li and titanium Ti in the system is 0.9:1, stir evenly and heat and boil for 1 to 3 hours. The resulting slurry is recorded as slurry A, and the solid in the slurry is the primary lithium supply product HLiTiO3 by the wet chemical method.

[0061] Step ②: Disperse 30 g to 75 g of lithium carbonate powder in 1 L of deionized water, stir evenly and slowly add tannic acid. Stop stirring when the slurry completely turns into a transparent viscous liquid. Stir for 1 to 3 hours. The resulting solution is recorded as solution B.

[0062] Step ③ Slowly pour solution B into slurry A under stirring conditions at room temperature to mix, control the molar ratio of lithium Li to titanium Ti in the slurry to be between 1.8:1, and stir for 1 hour to obtain slurry C. Slurry C is spray-dried with a hot air temperature of 200°C and an air outlet temperature of 100°C to obtain a mixed powder D.

[0063] Step ④: transfer the powder D to a muffle furnace for sintering. The sintering time is 5 to 10 hours and the sintering temperature is 500 to 900° C. After cooling in the furnace, the obtained solid is ground and crushed to obtain a high-temperature solid-phase secondary lithium supply product, namely, lithium metatitanate precursor Li2T iO3.

[0064] Step ⑤: Disperse the Li2TiO3 precursor in deionized water with a slurry concentration of 50g / L, and place it in a heating tank for stirring at a heating temperature of 50°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2 to 3 times. Dry the resulting filter cake at 60°C and crush it to obtain H2TiO3 lithium adsorbent.

[0065] Example 5: Figure 1 , Figure 2 Figure 3 Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, a method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps: during the preparation process, the dispersibility of the raw lithium source in the raw titanium source is improved by a secondary lithium supply method, the difficult-to-disperse lithium carbonate is converted into a soluble lithium salt, the diffusion resistance of lithium ions in the raw material is reduced, the raw lithium Li ions are distributed more evenly in the material, the utilization rate of the raw material is improved, and the adsorption capacity of the adsorbent is improved, organic acid molecules are introduced during the synthesis of the adsorbent precursor, and volatile gases are generated during the sintering process, so that the specific surface area of ​​the adsorbent is increased and the particle size distribution is more uniform.

[0066] A method for preparing a titanium-based lithium adsorbent with high adsorption capacity and high adsorption rate comprises the following steps:

[0067] Step (1), preparation of lithium metatitanate precursor: using metatitanate as a titanium source, lithium hydroxide and lithium carbonate as lithium sources, respectively, to prepare an adsorbent precursor by adopting a stepwise lithium supply method.

[0068] Step ①, place LiOH·H2O in a reaction container, pour in 500mL of deionized water and stir until dissolved. Slowly add a certain amount of metatitanic acid to the above solution, stir evenly and heat to boil, the resulting slurry is recorded as slurry A, and the solid in the slurry is the primary lithium supply product HLi TiO3 by the wet chemical method.

[0069] Step ②, disperse lithium carbonate powder in 1L deionized water, stir evenly and then slowly add tannic acid. Stop stirring when the slurry completely turns into a transparent viscous liquid. After stirring for a certain period of time, the resulting solution is recorded as solution B.

[0070] Step ③, slowly pour solution B into slurry A under stirring at room temperature to mix, and stir to obtain slurry C. Slurry C is spray-dried to obtain mixed powder D.

[0071] Step ④, transfer the powder D to a muffle furnace for sintering, and grind the obtained solid after cooling in the furnace to obtain a high-temperature solid-phase secondary lithium supply product, namely, lithium metatitanate precursor Li2T iO3.

[0072] Step (2), preparation of titanate-type adsorbent: Lithium Li in the precursor Li2TiO3 + After elution, H2T iO3 lithium adsorbent can be obtained. The specific operation is as follows: disperse the precursor in deionized water and place it in a heating tank for stirring. Add hydrochloric acid solution drop by drop to adjust the pH so that the slurry solution is always maintained between 1.4 and 2.5. Stop adding acid when the pH remains stable. Centrifuge to remove the supernatant and wash 2 to 3 times. Dry the obtained filter cake at 60°C and crush it to obtain H2T iO3 lithium adsorbent.

[0073] In step ①, the amount of LiOH·H2O used is 40-100 g. After adding metatitanic acid, the molar ratio of lithium Li to titanium Ti in the system is 0.9:1-1.3:1. The heating and stirring time is 1-3 hours.

[0074] The amount of lithium carbonate added in step ② is 30 to 75 g. The stirring time in the step is 1 to 3 hours.

[0075] In step ③, the molar ratio of lithium Li to titanium Ti in the slurry should be controlled between 1.8:1 and 2.3:1. The stirring time of the step is 1 to 5 hours. The hot air temperature of the spray drying is 140°C to 200°C, and the outlet air temperature is 80°C to 100°C.

[0076] In step ④, the sintering time is 5 to 10 hours, and the sintering temperature is 500 to 900°C.

[0077] In step (2), the concentration of the precursor slurry is 30-80 g / L, and the heating temperature is 40-70°C.

[0078] As described above, the embodiments of the present invention are described in detail, but it is obvious to those skilled in the art that many variations are possible as long as they do not deviate from the inventive point and effect of the present invention. Therefore, all such variations are also included in the protection scope of the present invention.

Claims

1. A method for preparing a titanium-based lithium adsorbent having high adsorption capacity and high adsorption rate, characterized in that , comprising the following steps: firstly, reacting a titanium source with a part of a lithium source under liquid conditions to prepare an intermediate with a high specific surface area, dissolving another part of the lithium source with an organic acid into a liquid lithium source, and then mixing the intermediate with the liquid lithium source, drying and sintering at a high temperature to prepare a titanium-based lithium adsorbent, and further comprising the following steps: Step 1, preparation of lithium metatitanate precursor: using metatitanate as a titanium source, lithium hydroxide and lithium carbonate as lithium sources, respectively, to prepare an adsorbent precursor by a step-by-step lithium supply method. Step ① Place 40g to 100g of lithium hydroxide monohydrate LiOH·H2O in a reaction container, pour in 500mL of deionized water and stir until dissolved, slowly add a certain amount of metatitanic acid to the above solution so that the molar ratio of lithium Li and titanium Ti in the system is 0.9:1 to 1.3:1, stir evenly and heat and boil for 1 to 3 hours, the resulting slurry is recorded as slurry A, and the solid in the slurry is the primary lithium supply product HLiTiO3 of the wet chemical method, Step ② Disperse 30g-75g lithium carbonate powder in 1L deionized water, stir evenly and slowly add tannic acid. Stop stirring when the slurry completely turns into a transparent viscous liquid. Stir for 1-3h. The resulting solution is recorded as solution B. Step ③: slowly pouring solution B into slurry A under stirring conditions at room temperature to mix, controlling the molar ratio of lithium Li to titanium Ti in the slurry to be between 1.8:1 and 2.3:1, stirring for 1 to 5 hours to obtain slurry C, spray drying slurry C, with a hot air temperature of 140°C to 200°C and an air outlet temperature of 80°C to 100°C, to obtain mixed powder D, Step ④: transfer the powder D to a muffle furnace for sintering, the sintering time is 5 to 10 hours, the sintering temperature is 500 to 900°C, and the obtained solid is ground and crushed after cooling in the furnace to obtain a high-temperature solid-phase method secondary lithium supply product, namely, lithium metatitanate precursor Li2TiO3. Step ⑤, disperse the Li2TiO3 precursor in deionized water with a slurry concentration of 50g / L, and place it in a heating tank for stirring at a heating temperature of 50°C, add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH1.4 and 2.5, stop adding acid when the pH remains stable, centrifuge to remove the supernatant, and wash 2 to 3 times, dry the resulting filter cake at 60°C and crush it to obtain H2TiO3 lithium adsorbent, Step 2, preparation of titanate-type adsorbent: After eluting the lithium Li+ in the lithium titanate precursor Li2TiO3, the H2TiO3 lithium adsorbent can be obtained. The specific operation is as follows: disperse the precursor in deionized water with a slurry concentration of 30-80 g / L, and place it in a heating tank with stirring at a heating temperature of 40-70°C. Add hydrochloric acid solution dropwise to adjust the pH so that the slurry solution is always maintained between pH 1.4 and 2.

5. When the pH remains stable, stop adding acid, centrifuge to remove the supernatant, and wash 2-3 times. Dry the resulting filter cake at 60°C and crush it to obtain the H2TiO3 lithium adsorbent.

2. The method for preparing a titanium-based lithium adsorbent having high adsorption capacity and high adsorption rate according to claim 1, characterized in that , comprising the following steps: in step ①, 73.84 g of LiOH·H2O is placed in a reaction container, and the molar ratio of lithium Li to titanium Ti is 1.1:

1.

3. The method for preparing a titanium-based lithium adsorbent having high adsorption capacity and high adsorption rate according to claim 2, characterized in that , comprising the following steps: in step ②, 59.11 g of lithium carbonate powder is dispersed in 1 L of deionized water.

4. The method for preparing a titanium-based lithium adsorbent having high adsorption capacity and high adsorption rate according to claim 2, characterized in that , comprising the following steps: in step ③, the molar ratio of Li to titanium Ti in the slurry is controlled to be 2.1:1, the hot air temperature is 140°C, the air outlet temperature is 80°C, and in step ④, the sintering time is 6h and the sintering temperature is 550°C.

Citation Information

Patent Citations

  • Lithium-rich manganese-based cathode material and preparation method thereof

    CN105489842A

  • Titanium-series lithium ion exchanger, and preparation method of precursor thereof

    CN110127756A